A Socio-Legal Analysis of University Students’ Perspectives on Challenges in Online Education and Protocols: Post-Covid Reflections - Sheer Abbas; Muhammad Yaseen (Emerging Science Journal, 2025)
The COVID-19 pandemic had a profound impact on nearly all sectors, including global education systems, necessitating a rapid shift from traditional classroom teaching to online learning, despite many institutions lacking the necessary infrastructure for such a transition. The integration of interactive multimedia and flexible scheduling in e-learning has enhanced student engagement and accessibility significantly compared to traditional education methods. It is crucial to assess the post-COVID impacts on students’ learning and performance following the abrupt shift from in-person to online education. The online questionnaire used here, created using Google Forms, targeted students across Pakistan, covering their opinions, challenges, and recommendations on traditional and online learning, particularly their post-COVID perspectives. Surveys were distributed to various universities, including institutions in Punjab, Sindh, Islamabad, Khyber Pakhtunkhwa, and Balochistan. A snowball sampling method was employed to gather responses, leveraging participants’ networks to expand the sample size, and the collected data were analyzed using the Statistical Package for the Social Sciences for descriptive statistics. The demographic attributes of the involved 150 respondents showed that 59.3% had a rural background, 80% were aged 18–23, and 75% were male, with 51% living within 1–25 km from their universities. Results revealed that students showed a slight preference for online education, with a higher level of comfort expressed in using digital tools and better access to resources, though factors of engagement and peer interaction still need improvement. Universities ought to address matters involving data privacy, academic integrity, accessibility, intellectual property, and contractual duties to ensure legal obedience and equity in online education. Faculty, students, and governing bodies should work jointly to design efficient legal strategies.